STRATEGI PROMOSI SEKTOR PARIWISATA PEMERINTAH KOTA MATARAM - N, Nurhayati (Universitas Riau Kepulauan, 2015)
Strategic management is the formulation of the comprehensive plan on how to promote tourism sector and to attract investors as done by the Department of Culture and Tourism of Mataram City to increase the number of tourist visits. One of the reasons to support this tourism sector is because it is very beneficial for the growth and the development of both central and local governments. Though it is understood that developing tourism is important, in practice there are a variety of fairly complex problems which require serious attention from the local government. Such problems as the promotion of tourism itself and the investments intended for tourism sector are common matters that often appear to the public. Based on this situation, the problems of the study are then formulated. They deal with the strategies of the Department of Culture and Tourism of Mataram City in the promotion and the investment on tourism sector and the ways to manage the promotion to attract the investments.This study aimed to: (1) know the strategies of the Department of Culture and Tourism of Mataram City, and (2) describe the promotion policies the tourism sector. The study used a qualitative approach in which the data were collected by library studies, observations and also interviews.The study concluded the followings. The strategies of the Department of Culture and Tourism of Mataram City to promote tourism and attract investment were varied. They included the promotion in national and international levels, the promotion through printed media and electronic media (internet), the promotion through exhibition and tourism events, art festivals and cultural performances on the tourism objects. The ways of doing the promotion were in the forms of improving the infrastructure on tourism objects, creating regulatory guidance and supervision of the business climate in tourism, and also developing cooperation with BPPD, IHRA, ASITA and other related institutions. The obstacles that the local government faced were related to the limited number of tourism objects that Mataram has especially when compared to the other regencies in the province of West Nusa Tenggara, the inadequate human resources on tourism, the limited number of tourism experts, the limited facility and infrastructure in the objects, the lack of public’s awareness on the importance of tourism, and lack of management of the street vendors in the tourism objects.The study provides some recommendations. Firstly, it is expected that the local government improves the promotion especially on the attractions or objects which are still unknown to many tourists and increase the awareness and the active participation of the community in the tourism activities as an effort to improve the quality of tourism attractions. Secondly, considering the poor quality and quantity of human resources in the tourism sector, the central and local governments are expected to seriously address the identified problems by professionally structuring the employees with consideration on the quality and quantity of the experts in the field of tourism.